The Positioning of the Social Anthropology Course in Social Work Education and the Practical Innovations in Teaching Methods - Liu, Moxian; Zhang, Yilie (Journal of Research in Vocational Education, 2025)
The Social Anthropology course plays a crucial role in social work education by fostering students' cultural sensitivity, cross-cultural communication, and social observation skills. However, current teaching practices face challenges such as unclear positioning, vague objectives, and outdated methods. This paper addresses these issues by clarifying the academic value and practical significance of Social Anthropology in social work education. It proposes a SMART-based framework for designing cognitive, skill-based, and affective learning objectives, alongside the integration of blended teaching methods, including case studies, fieldwork, flipped classrooms, and simulated scenarios. Practical results indicate that these reforms enhance students' theoretical analysis and practical competencies while strengthening their cultural sensitivity and social responsibility. Future recommendations include adopting more flexible and hybrid teaching approaches to further integrate theory and practice.